1979
DOI: 10.1243/emed_jour_1979_008_050_02
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of the Load in the Knee Joint with Special Reference to the Role of the Menisci

Abstract: The menisci of the knee joint transmit a considerable fraction of the total load acting on the joint. This paper describes an investigation into the load carrying capacity of the individual meniscus. Interest is also directed to an examination of the function of the degenerate meniscus and that of thc meniscus with different kinds of tears. Quantifying the meniscal loads is based on afour-spring model representing the load bearing areas in the knee with intact menisci. The assumptions underlying the model are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
4

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 0 publications
4
114
0
4
Order By: Relevance
“…Nevertheless, a 10%) difference in contact variables represents a significant reduction for the changes in the contact variables seen for the meniscectomized knee [2,4,6,19,28]. Peak contact stresses on the lateral and medial articular surfaces of the tibia increase over 300% in the meniscectomized knee [4,19,25,29], and contact areas decrease by 50% [4,10,19,25]. Thus, it is reasonable to assume that changes of only 10%) would reduce the rate of cartilage wear relative to that of the meniscectomized condition.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a 10%) difference in contact variables represents a significant reduction for the changes in the contact variables seen for the meniscectomized knee [2,4,6,19,28]. Peak contact stresses on the lateral and medial articular surfaces of the tibia increase over 300% in the meniscectomized knee [4,19,25,29], and contact areas decrease by 50% [4,10,19,25]. Thus, it is reasonable to assume that changes of only 10%) would reduce the rate of cartilage wear relative to that of the meniscectomized condition.…”
Section: Discussionmentioning
confidence: 99%
“…tension, compression, and shear stresses. The main functions are load transmission and shock absorption during dynamic movements (Walker and Erkman 1975, Shrive et al 1978, Seedhom and Hargreaves 1979. The menisci distribute stress over a large area of the articular cartilage.…”
Section: Meniscal Function-load Transmission and Shock Absorptionmentioning
confidence: 99%
“…In the same period of time, several biomechanical studies reported on the load bearing and shock absorbing functions of the menisci (Walker and Erkman 1975, Shrive et al 1978, Seedhom and Hargreaves 1979. It was now time to shift the paradigm to a more restrained attitude to total meniscectomy, 80 years after the introduction of the procedure.…”
Section: Partial Meniscectomymentioning
confidence: 99%
See 1 more Smart Citation
“…The main functions of the menisci are shock absorption and load transmission in the knee, mainly through distribution of mechanical stress over a large area of the joint cartilage (1)(2)(3)(4). Loss of meniscal function is recognized as a potent risk factor for both the development of knee osteoarthritis (OA) and cartilage loss in OA (5,6).…”
mentioning
confidence: 99%